Pengaruh Pengangguran Dan Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi Di Provinsi Bali - Fera Kristina; Friskilla Angeliani; Selince Restiani Omikang Malaifani; Nur Hayati; Farikha Ni'amah Hidayati; Lelahester Rina; Arief Sadjiarto (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
Economic growth is an effort made by the government to improve people's welfare. Factors that can affect economic growth are unemployment and HDI. This study aims to determine the effect of unemployment and HDI on economic growth in Bali Province. The method used is quantitative based on secondary data obtained by the Central Statistics Agency based on a 10 year time series. The results obtained are unemployment and HDI variables together have a significant influence on the variable economic growth. This is shown from the results of the F test calculation with a significance value of 0.000 <0.05. Partially the influence of the unemployment variable on economic growth based on the t test shows the results of sig 0.000 <0.05, which means that unemployment has a significant effect on economic growth in Bali Province. The results of the calculation of the HDI t-test on economic growth with a sig value of 0.159> 0.05, which means that the HDI variable has no significant effect on economic growth in Bali Province.